Evaluation of Exposure to Particulate Air Pollution and Airway Deposition in Cyclists in the Perth Metropolitan Area - Shrestha, Anu (Curtin University, 2019)
Cyclists may not be aware that they become exposed to high levels of air pollutants due to their increased ventilation rate and proximity to vehicular emissions. The study aimed to conduct spatial assessments to determine exposure to particulate air pollution in the lungs of cyclists in the Perth Metropolitan Area. The study involved four cycling routes, male and female cyclists. Participants cycling alone route 2 had the highest deposition of particles in the lungs.